2020
DOI: 10.1038/s41467-020-17489-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-lasting severe immune dysfunction in Ebola virus disease survivors

Abstract: Long-term follow up studies from Ebola virus disease (EVD) survivors (EBOV_S) are lacking. Here, we evaluate immune and gene expression profiles in 35 Guinean EBOV_S from the last West African outbreak, a median of 23 months (IQR [18-25]) after discharge from treatment center. Compared with healthy donors, EBOV_S exhibit increases of blood markers of inflammation, intestinal tissue damage, T cell and B cell activation and a depletion of circulating dendritic cells. All survivors have EBOV-specific IgG antibodi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…While the mechanisms underlying development of sequelae is not known, previous studies reported elevated levels of IL-8, TNF, and sCD163 in ZEBOV survivors compared to uninfected subjects (12). Therefore, to evaluate if BDBV survivors are characterized by a pro-inflammatory state, we measured 53 soluble markers associated with inflammation and immune activation in plasma.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the mechanisms underlying development of sequelae is not known, previous studies reported elevated levels of IL-8, TNF, and sCD163 in ZEBOV survivors compared to uninfected subjects (12). Therefore, to evaluate if BDBV survivors are characterized by a pro-inflammatory state, we measured 53 soluble markers associated with inflammation and immune activation in plasma.…”
Section: Resultsmentioning
confidence: 99%
“…While the causes of post-Ebola syndrome are not clear, direct tissue damage induced by viral persistence and replication and EBOV-induced auto-immunity are two possibilities. In this regard, ZEBOV survivors with long-term sequelae have higher EBOV-specific CD8+ and CD4+ T cells responses ( 11 ), potentially pointing to viral persistence, and ZEBOV survivors have long-lasting immune dysfunction characterized by cellular activation, increased levels of inflammatory markers and intestinal tissue damage compared to controls ( 12 ). Given that there are now thousands of EVD survivors, understanding the associations between the EBOV immune response and post-Ebola syndrome may help identify potential treatments.…”
Section: Introductionmentioning
confidence: 99%
“…sCD163 has been investigated as a biomarker for infection-associated HLH and MAS [ 72 , 91 , 93 , 94 , 112 ], though it is not included in HLH-2004 criteria or HScore. Elevated sCD163 has been linked to disease severity and mortality in viral infections of Ebola, HIV and Influenza and intriguingly these viruses are also associated with the development of HLH [ 80 , 86 , 87 , 88 , 89 ]. Levels of sCD163 were measured in severe sepsis patients by Feng et al which showed a peak median of 4190 ng/mL on day 5 of intensive care unit admission, Bleesing et al showed sCD163 levels in patients diagnosed with autoimmune-associated MAS to be 23,000 ng/mL, and Sadaat and Jang, indicated a level of 6384 ng/mL in a malignancy-related MAS patient [ 78 , 91 , 113 ].…”
Section: Nk Cell Activity Soluble Il-2 Receptor and Soluble Cd163mentioning
confidence: 99%
“…Ebola virus disease (EVD), caused by Ebola virus (EBOV; species: Zaire ebolavirus ), carries an extremely high case fatality rate, ranging from 40 to 70% in several outbreaks over the last decade [ 1 ]. EVD survivors frequently suffer from debilitating long-term sequelae, including musculoskeletal pain, neurocognitive deficits, depression, fatigue, ocular disorders, and immune dysfunction [ 2 , 3 , 4 , 5 ]. Apart from isolated laboratory accidents, all outbreaks originated from rural regions of Western and Middle Africa [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vaccines 2020, 8, x FOR PEER REVIEW 9 of 24 5. Could rVSVΔG-ZEBOV-GP have effects on biogeochemical cycles, particularly carbon and nitrogen recycling through changes in soil decomposition of organic material?…”
mentioning
confidence: 99%